2019
DOI: 10.1016/j.memsci.2019.03.076
|View full text |Cite
|
Sign up to set email alerts
|

Towards the dehydration of ethanol using pervaporation cross-linked poly(vinyl alcohol)/graphene oxide membranes

Abstract: Highly hydrophilic inorganic material graphene oxide (GO) was successfully prepared and incorporated into a cross-linked poly(vinyl alcohol) (PVA) matrix. The obtained mixed matrix membranes (MMMs) have been used for the dehydration of ethanol (10:90% water-ethanol) by pervaporation (PV), monitoring their performance in terms of total permeate flux, partial components fluxes, as well as their separation factor. The effect of filler was analyzed by doubling the GO content (at 0.5, 1.0, and 2.0 wt.%) in the MMMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 196 publications
(78 citation statements)
references
References 61 publications
(105 reference statements)
2
74
1
1
Order By: Relevance
“…The separation factors of the crosslinked GO membranes for various conditions are shown in Figure 7. Our separation factors are modest compared with those reported by others, such as Hua et al for aldehyde-crosslinked GO membranes [31] and Castro-Muñoz et al for PVA membranes incorporated with GO [53]. This is owing to the relatively high amount of ethanol diffusing into the permeate for our membranes, which is in the range of 55-65 wt% of permeate ( Figure 6) compared, for example, with 10-20% reported by Hua et al for feeds with similar (85% ethanol) composition [31].…”
Section: Ethanol-water Mixturescontrasting
confidence: 84%
“…The separation factors of the crosslinked GO membranes for various conditions are shown in Figure 7. Our separation factors are modest compared with those reported by others, such as Hua et al for aldehyde-crosslinked GO membranes [31] and Castro-Muñoz et al for PVA membranes incorporated with GO [53]. This is owing to the relatively high amount of ethanol diffusing into the permeate for our membranes, which is in the range of 55-65 wt% of permeate ( Figure 6) compared, for example, with 10-20% reported by Hua et al for feeds with similar (85% ethanol) composition [31].…”
Section: Ethanol-water Mixturescontrasting
confidence: 84%
“…3A and B. The diffraction peaks of GO and Sm-MOF were the same as those reported in literature 28,30 and appeared in the XRD patterns of the Sm-MOF/GO composites. As shown in Fig.…”
Section: Characterization and Mechanismsupporting
confidence: 78%
“…The authors reported that the enhancement was attributed to the formation of hydrogen bonds between PVP and GO. Besides improving the hydrophilicity of membranes; GO has been also identified as a potential candidate to enhance the water transport of membranes according to its unimpeded water permeation properties [83][84][85]. Finally, some other nanomaterials are also providing good insights to mitigate the fouling in membranes.…”
Section: Qac/carbonmentioning
confidence: 99%